TOWARDS THE BEST MODEL GOOD CORPORATE GOVERNANCE AND KNOWLEDGE MANAGEMENT TO IMPROVE PERFORMANCE THROUGH JOB SATISFACTION - Karyatun, Subur; Yuliantini , Tine; Saratian, Eko; Paijan, Paijan; Soelton, Mochamad; Riadi, Elvira (Faculty of Economic and Business, University of Pasundan, 2023)
The purpose of this study was to examine and assess the impact of Good Corporate Governance and Knowledge Management on Organizational Citizenship Behavior through the mediation of Job Satisfaction. Quantitative research using questionnaire collection techniques and SEM Smart-PLS, with a saturated sample of 86 employees. Finding, Good Corporate Governance has no effect on Organizational Citizenship Behavior, Knowledge Management has a significant effect on Organizational Citizenship Behavior, Good Corporate Governance and Knowledge Management has a significant effect on Job Satisfaction. Job satisfaction does not mediate the effect of good corporate governance on Organizational Citizenship Behavior, but is able to mediate the relationship between Knowledge Management and Organizational Citizenship Behavior. Interestingly, good company GCG does not necessarily increase employee OCB. GCG which still seems to be carried out only by decision makers in a directed manner so that employees do not feel they are part of the GCG implementation in the company.